Environmental drivers of Cheirogaleidae population density: Remarkable resilience of Madagascar's smallest lemurs to habitat degradation. Issue 11 (2nd May 2021) - Hending, Daniel
Abstract: Aim: Global animal populations are in decline due to destruction and degradation of their natural habitat. Understanding the factors that determine the distribution and density of threatened animal populations is therefore now a crucial component of their study and conservation. The Cheirogaleidae are a diverse family of small‐bodied, nocturnal lemurs that are widespread throughout the forests of Madagascar. However, many cheirogaleid lemurs are now highly threatened with extinction and the environmental factors that determine their distribution and population density are still little known. Here, I investigated the environmental drivers of Cheirogaleidae population density at genus level. Location: Various forest sites across Madagascar. Methods: I investigated how six environmental variables affect Cheirogaleidae population density at the genus level via random‐effect meta‐analyses. I then used a generalized linear mixed‐effects model to identify the primary predictors of Cheirogaleidae population density. Finally, I investigated how the population density of this family of lemurs varies between protected and unprotected areas of Madagascar via a GLM analysis. Results: My results indicate that the relationships between the tested environmental factors and population density are genus‐specific among the Cheirogaleidae. Rather remarkably, the density of Microcebus appears to have a profoundly positive relationship with anthropogenic disturbance and a negative relationship with forest cover, a finding that is also reflected by larger population densities within unprotected areas in comparison with localities within Madagascar's protected area network. Main Conclusions: The results of this study are highly encouraging for the conservation of the Cheirogaleidae and highlight the remarkable resilience of these lemurs to habitat degradation and anthropogenic activity. However, this study also outlines the dearth of knowledge that we have for many species, and why these data are urgently needed to understand the biogeography and ecology of threatened animal populations and implement successful conservation. Abstract : In this manuscript, I investigated the primary environmental drivers of population density in the Cheirogaleidae, a family of small, nocturnal, and understudied primates that are endemic to Madagascar. My results indicate that the relationships between the tested environmental factors and population density are genus‐specific among the Cheirogaleidae, and this is likely due to the natural histories and ecological niches of each respective genus. Further, forest quality and anthropogenic disturbance do not appear to negatively influence Cheirogaleidae density, which remains high outside of protected areas; this is a highly encouraging finding for this group of threatened primates.